2007
DOI: 10.1074/jbc.m703231200
|View full text |Cite
|
Sign up to set email alerts
|

The ADAM10 Prodomain Is a Specific Inhibitor of ADAM10 Proteolytic Activity and Inhibits Cellular Shedding Events

Abstract: ADAM10 is a disintegrin metalloproteinase that processes amyloid precursor protein and ErbB ligands and is involved in the shedding of many type I and type II single membrane-spanning proteins. Like tumor necrosis factor-␣-converting enzyme (TACE or ADAM17), ADAM10 is expressed as a zymogen, and removal of the prodomain results in its activation. Here we report that the recombinant mouse ADAM10 prodomain, purified from Escherichia coli, is a potent competitive inhibitor of the human ADAM10 catalytic/disintegri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 134 publications
(131 citation statements)
references
References 31 publications
7
124
0
Order By: Relevance
“…This strongly suggests that ADAM10 is also responsible for the constitutive release of endogenous IL-6R in the mouse. We also assessed constitutive IL-6R shedding in the presence of recombinant murine ADAM10 prodomain, which has been reported to effectively block ADAM10 activity in the mouse (20). Supporting our results with pharmacological inhibitors we also noticed a substantial reduction of constantly released IL-6R when murine ADAM10 was blocked by the inhibitory prodomain (Fig.…”
Section: Adam17 Is the Major Sheddase Of Pma-and Lps-induced Il-6r Shsupporting
confidence: 80%
See 1 more Smart Citation
“…This strongly suggests that ADAM10 is also responsible for the constitutive release of endogenous IL-6R in the mouse. We also assessed constitutive IL-6R shedding in the presence of recombinant murine ADAM10 prodomain, which has been reported to effectively block ADAM10 activity in the mouse (20). Supporting our results with pharmacological inhibitors we also noticed a substantial reduction of constantly released IL-6R when murine ADAM10 was blocked by the inhibitory prodomain (Fig.…”
Section: Adam17 Is the Major Sheddase Of Pma-and Lps-induced Il-6r Shsupporting
confidence: 80%
“…Cells were stimulated with PMA or LPS from Escherichia coli O111:B4 (both Sigma) as depicted in the figure legends. Generation of neutralizing, bivalent ADAM17 antibody D1(A12) and recombinant murine ADAM10 prodomain were described previously (19,20). The hydroxamate-based ADAM inhibitors GI254023X and GW280264X were synthesized by Iris Biotech (Marktredwitz, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…ADAM10 is expressed as an inactive prodomain containing zymogene, which is activated by the proprotein convertases furin and PC7 (14). The prodomain is important for folding of ADAM10 and acts as a potent inhibitor of ADAM10 activity (14,15). Recently, it was demonstrated that ADAM10 transcription is stimulated by all-trans retinoic acid and by the deacetylase Sirtuin1 (16,17).…”
mentioning
confidence: 99%
“…S1A) was capable of ADAM10-dependent BTC shedding and the generation of a stable, cellular BTC remnant (termed BTC-CTF) (Moss et al, 2007). To investigate the biological significance of the BTC-CTF in IMPE cells expressing BTC-WT (IMPE-BTC-WT), we first verified that proBTC was correctly processed to produce BTC-CTF (Moss et al, 2007;Sanderson et al, 2006a;Sanderson et al, 2005).…”
Section: +mentioning
confidence: 99%
“…We have previously demonstrated that the extracellular domain of proBTC can be proteolytically cleaved by ADAM10 to release the mature, active ligand and to produce a stable, cellular BTC remnant (termed BTC-CTF) (Moss et al, 2007;Sanderson et al, 2006a;Sanderson et al, 2005). Because of its stability, BTC-CTF represents a significant proportion of the cellular BTC isoforms expressed in cells under steady-state conditions.…”
Section: Introductionmentioning
confidence: 99%